Termination Of Employment (PHK) And The Realization Of Severance Rights From The Perspective Of Labor Law - Fatria Ntobuo, Deby (Universitas Negeri Gorontalo, 2024)
Termination of Employment (PHK) is a critical issue in the world of labor that often leads to conflicts between workers and employers. This study aims to examine the process of PHK and the implementation of workers' severance rights from the perspective of Indonesian labor law, particularly based on Law No. 13 of 2003 on Employment and the Job Creation Law. The research method used is juridical-normative with an approach to regulations and case studies. The results of the study show that the PHK process must be carried out in good faith and through mechanisms regulated by law, such as mediation and bipartite negotiations. However, in practice, many PHK cases do not meet legal procedures, resulting in harm to workers, including the failure to fulfill severance rights fairly. The Job Creation Law introduces several changes that may offer flexibility to employers but also create new challenges regarding the protection of workers' rights. This study recommends strengthening labor supervision and enhancing legal understanding for both workers and employers to create a harmonious industrial relationship.